The influence of vitamin-C intake on blood glucose measurements in COVID-19 pandemic - Zaid Mahdi Jaber Al-Obaidi; Yasmeen Ali Hussain; Alaa A Ali; Mohammed Dakhil Al-Rekabi (Journal of Infection in Developing Countries)
Introduction: Coronavirus disease 2019 (COVID-19) is declared as pandemic by the World Health Orgnazation (WHO) on March 2020. One of the heavily utilized measures during this pandemic is vitamin C (aka ascorbic acid). Unfortunately, vitamin C has been associated with glucose measurement interference and thus this study highlights the elevated levels of blood glucose correlated with the presence of vitamin C interference.